Leisure and the Motive to Volunteer: Theories of Serious, Casual, and Project-Based Leisure - Stebbins, Robert A. author. aut Link
VI, 82 p.
Keywords: Volunteering and its nonprofit organizations have commonly been analyzed in economic terms, with volunteering being referred to as "unpaid (productive) work". This economic definition has been around far longer than that of volunteering conceived of as leisure, which is discussed as the volitional definition. By means of a lengthy literature review, this book sets out the theoretical and empirical contributions of the serious leisure perspective to understanding volunteer motivation. This second approach began more than 40 years ago. It answers the key motivational question of why people engage in unpaid productive work, laborious or not. Since in this conception payment in cash or in kind is not an incentive to perform such work, what encourages people to volunteer? The serious leisure perspective, unlike mainstream economics, can shed considerable light on this question.